ANTIMICROBIAL RESISTANCE PATTERN OF CLINICAL BACTERIAL ISOLATES AT THE EAST KALIMANTAN PROVINCIAL HEALTH LABORATORY, 2024 - Rahmadi; Riyan Ningsih; Blego Sedionoto (Faculty of Public Health Mulawarman University, Indonesia, 2025)
The rising incidence of infections caused by antimicrobial-resistant bacteria has become a serious public health concern in Indonesia, yet data on resistance patterns in East Kalimantan, particularly in Samarinda, remain limited. This study aimed to describe antimicrobial resistance patterns among clinical bacterial isolates examined at the East Kalimantan Provincial Health Laboratory (UPTD Labkes) in 2024 through a descriptive observational design using secondary data from culture results and antibiotic susceptibility testing of 201 clinical isolates collected from January to December 2024. Data were analyzed descriptively using tabulation and percentage distribution. Of all positive isolates, 54.4% were Gram-negative bacteria and 45.6% were Gram-positive, with Escherichia coli being the most frequently identified species (24.4%), followed by Staphylococcus haemolyticus (7.0%) and Pseudomonas aeruginosa (7.0%). Susceptibility testing indicated that E. coli exhibited high sensitivity to meropenem (98%) and amikacin (100%), whereas Staphylococcus aureus demonstrated oxacillin resistance of 30.8%, suggesting the presence of MRSA. The predominant resistance mechanisms detected included β-lactamase production (21.7%), ESBL (40.6%), and MRSA (37.7%). These findings highlight substantial variability in bacterial susceptibility patterns in Samarinda and provide an essential baseline for strengthening continuous antimicrobial resistance surveillance efforts.